One-month humoral response following two or three doses of messenger RNA coronavirus disease 2019 vaccines as primary vaccination in specific populations in France: first results from the Agence Nationale Recherche contre le Sida (ANRS)0001S COV-POPART cohort. (March 2023) - Loubet, Paul; Wittkop, Linda; Ninove, Laetitia; Chalouni, Mathieu; Barrou, Benoit; Blay, Jean-Yves; Hourmant, Maryvonne; Thouvenot, Eric; Laville, Martine; Laviolle, Bruno; Lelievre, Jean-Daniel; Morel, Jacques; et al.
Abstract: Objectives: : We aimed to investigate the 1-month humoral response to two or three doses of a messenger RNA coronavirus disease 2019 (COVID-19) vaccine as a primary vaccination regimen in specific populations compared with that in healthy adults. Methods: Agence Nationale Recherche contre le Sida (ANRS)0001S–COV-POPART (NCT04824651) is a French nation-wide, multi-centre, prospective, observational cohort study assessing the immune response to COVID-19 vaccines routinely administered to 11 sub-groups of patients with chronic conditions and two control groups. Patients and controls who received at least two vaccine doses and whose results 1 month after the second dose were available were included. The humoral response was assessed 1 month after the first, second and third doses (if applicable) based on the percentage of responders (positive for anti-Spike severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2] IgG antibodies), geometric means of anti-Spike SARS-CoV-2 IgG antibodies (enzyme-linked immunosorbent assay) and proportion of participants with anti-SARS-CoV-2-specific neutralizing antibodies ( in vitro neutralization assay for the original SARS-CoV-2 strain). All analyses were centralized. Results: We included 4091 participants in this analysis: 2979 participants from specific sub-populations and 1112 controls. Only 522 (17.5%) participants from the specific populations received three doses as a primary vaccination regimen. Patients living with human immunodeficiency virus, cancer and diabetes had high percentages of responders after two doses, whereas patients with solid organ transplants, allogeneic hematopoietic stem cell transplants and hypogammaglobulinaemia had the lowest percentage of responders (35.9% [95% CI, 29.2–43.0], 57.4% [95% CI, 48.1–66.3] and 77.1% [95% CI, 65.6–86.3], respectively). In those who received the third dose, the percentage of responders reached 54.2% (95% CI, 42.9–65.2) (vs. 32.3% [95% CI, 16.7–51.4] after 2 doses) among those with solid organ transplants and 73.9% (95% CI, 58.9–85.7) (vs. 56.1% [95% CI, 46.2–65.7] after 2 doses) among those with hematopoietic stem cell transplants. Similar results were found with anti-SARS-CoV-2-specific neutralizing antibodies. Conclusions: A lower humoral response to COVID-19 vaccines was observed in the specific populations compared with that in the controls. The third dose of this vaccine in the primary regimen had a positive effect on the percentages of patients who developed anti-Spike IgG antibodies and specific neutralizing antibodies.